2022
DOI: 10.1111/liv.15163
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and metabolic dysfunction‐associated fatty liver disease: Is there a link?

Abstract: Non-alcoholic fatty liver disease (NAFLD), recently re-defined and re-classified as metabolic dysfunction-associated fatty liver disease (MAFLD), has become increasingly prevalent and emerged as a public health problem worldwide. To date, the precise pathogenic mechanisms underpinning MAFLD are not entirely understood, and there is no effective pharmacological therapy for NAFLD/MAFLD. As a newly discovered form of iron-dependent programmed cell death, ferroptosis can be involved in the development and progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 66 publications
0
35
0
Order By: Relevance
“…32 In addition, hepatic iron overload was found to induce oxidative stress and lipid peroxidation by producing reactive oxygen species, consequently triggering ferroptosis. 33 Tsurusaki et al confirmed that hepatic ferroptosis triggers the initiation of inflammation in mice with steatohepatitis. 8 The dysfunction of iron metabolism and involvement of lipid peroxidation in the association between ferroptosis and MAFLD, and the role of iron-chelating agents in the alleviation of histopathological lesions and reduction of hepatic inflammation in mice, were highlighted in further experimental evidence.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…32 In addition, hepatic iron overload was found to induce oxidative stress and lipid peroxidation by producing reactive oxygen species, consequently triggering ferroptosis. 33 Tsurusaki et al confirmed that hepatic ferroptosis triggers the initiation of inflammation in mice with steatohepatitis. 8 The dysfunction of iron metabolism and involvement of lipid peroxidation in the association between ferroptosis and MAFLD, and the role of iron-chelating agents in the alleviation of histopathological lesions and reduction of hepatic inflammation in mice, were highlighted in further experimental evidence.…”
Section: Discussionmentioning
confidence: 97%
“…Hepatic iron quantified using MRI‐based R2* was reported to be associated with liver fibrosis, hepatic inflammation and ballooning, 6 which may be partly explained by the disruption of the balance between M1/M2 macrophage polarization and the activation of M1 macrophages 32 . In addition, hepatic iron overload was found to induce oxidative stress and lipid peroxidation by producing reactive oxygen species, consequently triggering ferroptosis 33 . Tsurusaki et al confirmed that hepatic ferroptosis triggers the initiation of inflammation in mice with steatohepatitis 8 .…”
Section: Discussionmentioning
confidence: 99%
“…As a newly discovered form of iron-dependent programmed cell death, ferroptosis is involved in the development and progression of NAFLD. 50 A typical feature of NAFLD is the development of oxidative stress and redox imbalance. 51 In recent years, an increasing number of studies reported that coenzyme A is closely related to NAFLD from different perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Liver fibrosis refers to an intricate pathological process in the liver characterized by excessive accumulation of extracellular matrix ( 121 ). It has an intimate association with chronic liver damage and acts as a significant intermediate pathogenetic link of multiple chronic liver disorders, such as NAFLD ( 122 ). If not treated timely, liver fibrosis putatively leads to more detrimental events, including cirrhosis, liver failure, HCC, and even death.…”
Section: The Role Of Ferroptosis In Nafldmentioning
confidence: 99%